In situ cosmogenic (10)Be production-rate calibration from the Southern Alps, New Zealand RID D-4720-2011 - Putnam, A. E.; Schaefer, J. M.; Barrell, D. J. A.; Vandergoes, M.; Denton, G. H.; Kaplan, M. R.; Finkel, R. C.; Schwartz, R.; Goehring, B. M.; Kelley, S. E. (Quaternary Geochronology, 2010)
We present a (10)Be production-rate calibration derived from an early Holocene debris-flow deposit at about 1000 m above sea level in the central Southern Alps, New Zealand, in the mid-latitude Southern Hemisphere. Ten radiocarbon ages on macrofossils from a soil horizon buried by the deposit date the deposit to 9690 +/- 50 calendar years before AD2008. Surface (10)Be concentrations of seven large boulders partially embedded in the stable surface of the deposit are tightly distributed, yielding a standard deviation of similar to 2%. Conversion of the (10)Be measurements to sea level/high-latitude values using each of five standard scaling methods indicates (10)Be production rates of 3.84 +/- 0.08, 3.87 +/- 0.08, 3.83 +/- 0.08, 4.15 +/- 0.09, and 3.74 +/- 0.08 atoms g(-1) a(-1), relative to the '07KNSTD' (10)Be AMS standard, and including only the local time-integrated production-rate uncertainties. When including a sea level high-latitude scaling uncertainty the overall error is similar to 2.5% (1 sigma) for each rate. To test the regional applicability of this production-rate calibration, we measured (10)Be concentrations in a set of nearby moraines deposited before 18060 +/- 200 years before AD2008. The (10)Be ages are only consistent with minimum-limiting (14)C age data when calculated using the new production rates. This also suggests that terrestrial in situ cosmogenic-nuclide production did not change significantly from Last Glacial Maximum to Holocene time in New Zealand. Our production rates agree well with those of a recent calibration study from northeastern North America, but are 12-14% lower than other commonly adopted values. The production-rate values presented here can be used elsewhere in New Zealand for rock surfaces exposed during or since the last glacial period. (C) 2009 Elsevier B.V. All rights reserved.
id: 2031; PT: J; UT: WOS:000280946500002

In situ cosmogenic Be-10 production-rate calibration from the Southern Alps, New Zealand - Putnam, A. E.; Schaefer, J. M.; Barrell, D. J. A.; Vandergoes, M.; Denton, G. H.; Kaplan, M. R.; Finkel, R. C.; Schwartz, R.; Goehring, B. M.; Kelley, S. E. (QUATERNARY GEOCHRONOLOGY, 2010)
We present a Be-10 production-rate calibration derived from an early Holocene debris-flow deposit at about 1000 m above sea level in the central Southern Alps, New Zealand, in the mid-latitude Southern Hemisphere. Ten radiocarbon ages on macrofossils from a soil horizon buried by the deposit date the deposit to 9690 +/- 50 calendar years before AD2008. Surface Be-10 concentrations of seven large boulders partially embedded in the stable surface of the deposit are tightly distributed, yielding a standard deviation of similar to 2%. Conversion of the Be-10 measurements to sea level/high-latitude values using each of five standard scaling methods indicates Be-10 production rates of 3.84 +/- 0.08, 3.87 +/- 0.08, 3.83 +/- 0.08, 4.15 +/- 0.09, and 3.74 +/- 0.08 atoms g(-1) a(-1), relative to the `07KNSTD' Be-10 AMS standard, and including only the local time-integrated production-rate uncertainties. When including a sea level high-latitude scaling uncertainty the overall error is similar to 2.5% (1 sigma) for each rate. To test the regional applicability of this production-rate calibration, we measured Be-10 concentrations in a set of nearby moraines deposited before 18060 +/- 200 years before AD2008. The Be-10 ages are only consistent with minimum-limiting C-14 age data when calculated using the new production rates. This also suggests that terrestrial in situ cosmogenic-nuclide production did not change significantly from Last Glacial Maximum to Holocene time in New Zealand. Our production rates agree well with those of a recent calibration study from northeastern North America, but are 12-14% lower than other commonly adopted values. The production-rate values presented here can be used elsewhere in New Zealand for rock surfaces exposed during or since the last glacial period. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Be-10; C-14; Cosmogenic nuclide; Debris flow; Holocene; Last glacial maximum; Moraine; Production rate; South Island

In situ cosmogenic 10Be production-rate calibration from the Southern Alps, New Zealand - Putnam, A. E.; Schaefer, J. M.; Barrell, D. J. A.; Vandergoes, M.; Denton, G. H.; Kaplan, M. R.; Finkel, R. C.; Schwartz, R.; Goehring, B. M.; Kelley, S. E. (Quaternary Geochronology, 2009)
id: 840In pressY

The deglaciation of eastern Maine: in Deglacial history and relative sea-level changes, northern New England and adjacent Canada - Dorion, C. C.; Kaplan, M. R.; Kreutz, K. J.; Balco, G.; Wright, J.; Borns, H. W., Jr. (Deglacial history and relative sea-level changes, northern New England and adjacent Canada, 2001)
id: 1310

Stratigraphy, paleoceanography, chronology, and paleoenvironment during deglaciation of eastern Maine, Report - Dorion, C. C.; Balco, G.; Kaplan, M. R.; Kreutz, K. J.; Wright, J.; Borns, H. W. (Deglacial History and Relative Sea Level Changes, Northern New England and adjacent Canada, 2001)
id: 1333